Survival and complications of cytoreductive surgery with hyperthermic intraperitoneal chemotherapy in patients with intra-abdominal malignancies: A meta-analysis of randomized controlled trials - Changchun Jian; Changchun Jian; Hai Mou; Hai Mou; Ye Zhang; Ye Zhang; Qingxin Fan; Qingxin Fan; Yunsheng Ou; Yunsheng Ou (Frontiers Media S.A., 2023)
Background: Peritoneal metastasis (PM) is an advanced stage of intra-abdominal malignancy with a very poor prognosis. In recent years, hyperthermic intraperitoneal chemotherapy (HIPEC) combined with cytoreductive surgery (CRS) has been utilized as an active treatment in the prevention and treatment of PM, with encouraging results. However, compared with CRS alone, the results of the CRS plus HIPEC strategy in the treatment of patients with intra-abdominal malignancies are still controversial. This study sought to determine the impact of HIPEC + CRS on patient survival and adverse events (AEs) by reviewing randomized controlled trials (RCTs) for all types of intra-abdominal malignancies.Methods: A PubMed, Embase, Cochrane Library, Web of Science and Clinical Trials.gov search extracted all RCTs until 12 October 2022, examining the CRS + HIPEC vs. CRS alone strategies in the treatment of various types of intra-abdominal malignancies. The outcomes included overall survival (OS), disease-free survival (DFS), relapse-free survival (RFS), progression-free survival (PFS) and AEs. The dichotomous data were pooled and reported as odds ratios (ORs) with 95% confidence intervals (CIs). The survival outcome data were pooled using hazard ratios (HRs) and corresponding 95% CIs. The Cochrane Collaboration's Risk of Bias Tool was used to assess the risk of bias in the included studies.Results: A total of 12 RCTs were included in this meta-analysis, including 873 patients in the CRS + HIPEC group and 878 patients in the CRS alone group. The studies included 3 (617 patients) on colorectal cancer, 4 (416 patients) on gastric cancer, and 5 (718 patients) on ovarian cancer. Our analysis showed no difference in OS between the CRS + HIPEC and CRS alone groups (HR: 0.79, 95% CI 0.62-1.01). Subgroup analysis showed that CRS + HIPEC improved the OS of gastric cancer patients (HR: 0.49, 95% CI 0.32-0.76) compared with CRS alone. However, CRS + HIPEC did not significantly improve the OS of colorectal cancer (HR: 1.06, 95% CI 0.81-1.38) and ovarian cancer (HR: 0.82, 95% CI 0.62-1.07) patients. In addition, there was no significant difference in DFS/RFS (HR: 0.78, 95% CI 0.57-1.07) or PFS (HR: 1.03, 95% CI 0.77-1.38) between the two groups. Compared with CRS alone, CRS with HIPEC had greater nephrotoxicity (OR: 0.45, 95% CI 0.21-0.98), while other AEs did not differ significantly between the two groups.Conclusion: Our results suggest that CRS + HIPEC may improve OS in gastric cancer patients compared with CRS alone, but we did not observe a benefit for DFS/RFS. For patients with ovarian and colorectal cancers, our results suggest that HIPEC + CRS does not appear to improve survival outcomes. In addition, CRS + HIPEC has higher nephrotoxicity than CRS alone. More evidence from RCTs is needed to evaluate whether the use of CRS + HIPEC is an appropriate option.